Pengaruh Budaya Organisasi Dan Kepuasan Kerja terhadap Komitmen Organisasional Karyawan - Fransiska Ekobelawati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2019)
This study was aimed to determine: (1) Organization culture of Waroeng Spesial Sambal Yogyakarta;(2) Employee’s job satisfaction of the Sari Banto Pontianak; (3) Employee’s organizational commitment ofthe Waroeng Spesial Sambal; (4) The effect of organization culture on employee’s organizationalcommitment of the Sari Banto Pontianak; (5) The effect of job satisfaction on employee’s organizationalcommitment of the Sari Banto Pontianak; (6) The effect of organization culture and job satisfaction onemployee’s organizational commitment of the Sari Banto Pontianak. The sample in this study were 100employees of the Sari Banto Pontianak. The data collection technique used was questionnaire. The dataanalysis technique used was multiple regression.The results of this study indicated that: (1) There was positive and significant relationship betweenorganization culture on employee’s organizational commitment of the Sari Banto Pontianak in the amount of(β) 0,513 (***p<0,001; p=0,000), with the contribution of organization culture on employee’sorganizational commitment in the amount of (ΔR2) 0,243; (2) There was positive and significant relationshipbetween job satisfaction on employee’s organizational commitment of the Sari Banto Pontianak in theamount of (β) 0,213 (*p<0,05; p=0,034), with the contribution of job satisfaction on employee’sorganizational commitment in the amount of (ΔR2) 0,044; (3) There was positive and significant influencebetween the variables of organization culture and job satisfaction on employee’s organizational commitmentof the Sari Banto Pontianak in the amount of organization culture (β) 0,512 (***p<0,001; p=0,000) and jobsatisfaction (β) 0,210 (*p<0,05; p=0,015). The influence of organization culture and job satisfaction toemployee’s oranizational commitment of the Sari Banto Pontianak (ΔR2) 0,286*.<!–End